Roles of RNA Methylation on Tumor Immunity and Clinical Implications - Zhang, Maorun; Song, Junmin; Yuan, Weitang; Zhang, Wei; Sun, Zhenqiang (Frontiers in Immunology, 2021)
RNA methylation is a kind of RNA modification that exists widely in eukaryotes and prokaryotes. RNA methylation occurs not only in mRNA but also in ncRNA. According to the different sites of methylation, RNA methylation includes m6A, m5C, m7G and 2-O-methylation modifications. Modifications affect the splicing, nucleation, stability and immunogenicity of RNA. RNA methylation is involved in many physiological and pathological processes. In the immune system, especially for tumour immunity, RNA methylation affects the maturation and response function of immune cells. Through the influence of RNA immunogenicity and innate immune components, modifications regulate the innate immunity of the body. Some recent studies verified that RNA methylation can regulate tumour immunity, which also provides a new idea for the future of treating immunological diseases and tumour immunotherapy.